Ameliorative effect of probiotic fermented Litchi chinensis juice on phytochemical composition and oxidative stress-linked diabetes - Shanti Bhushan Mishra; Shradhanjali Singh; Nishesh Sharma; Mitasha Srivastava (Discover Food)
Abstract The present study was designed to analyze the effect of fermentation (natural and commercial probiotic fermentation) on phytochemical composition and the antidiabetic effect of Litchi chinensis juice. The Litchi juices underwent natural fermentation (NFLJ) and commercial probiotic fermentation (CFLJ), while a control group of fresh Litchi chinensis juice (LCJ) was processed without fermentation for comparison. Various physicochemical and phytochemical characteristics including pH, total acidity, reducing sugar, total alkaloid content, tannin content, total phenolic and flavonoid contents were measured. In vitro, antioxidant activity was evaluated through tests for nitric oxide and DPPH scavenging activity, while the levels of SOD, CAT, GST, and GPx, as well as lipid profiles such as cholesterol, triglycerides, HDL, and LDL, were determined using diagnostic kits. The study also assessed the antidiabetic effects of fermented Litchi juices by testing them on Streptozotocin- high-fat diet induced diabetes in rats.The findings indicated that both the fermented Litchi juices (NFLJ, and CFLJ) demonstrated significantly higher antioxidant capacities compared to the control LCJ. Fermentation resulted in enhanced phenol and flavonoid content. Additionally, fermented juices were found to have a strong antidiabetic effect by reducing blood glucose levels and increasing the activity of antioxidant enzymes. Fermentation significantly enhanced the antioxidant and antidiabetic properties of Litchi chinensis juices, suggesting that both natural and commercial probiotic fermentation could be effective methods for improving the health benefits of Litchi juices. The finding of the present study supports that fermentation can not only aid food preservation but can also improve bioactive potential.